Determination of Burnout Through Work Life Balance, Job Stress, and Digital Stress in Private University Lecturers - Noviardi Ferzi; Albetris; Muhammad Akbar (Fundamental and Applied Management Journal, 2025)
The acceleration of digitalization in higher education has increased work demands on lecturers, particularly through technology-based administration, continuous information flow, and expectations of rapid responsiveness. This study examines the effects of work-life balance, job stress, and digital stress on burnout and their impact on job satisfaction among private university lecturers in the LLDIKTI X region. Grounded in the Job Demands-Resources model, this research adopts a quantitative approach using Structural Equation Modeling (PLS) based on survey data collected from lecturers. The results show that job stress and digital stress significantly increase burnout, while work-life balance is also associated with higher burnout in the context of blurred work–life boundaries. Job stress reduces job satisfaction, whereas digital stress exhibits a dual effect by increasing both burnout and job satisfaction, indicating its role as both a hindrance and challenge demand. Burnout is identified as a key mediating variable linking work pressures to job satisfaction. Substantively, higher burnout leads to lower job satisfaction, confirming its central role in the health impairment process. This study contributes to the literature by extending the Job Demands-Resources model through the inclusion of digital stress as a contemporary work demand and by highlighting the complexity of lecturer well-being in the digital academic environment. The findings provide important implications for university management in designing policies that balance digital demands, support lecturer well-being, and sustain academic performance.